Impactos das ferramentas de manufatura enxuta nas condições ergonômicas de trabalho: uma revisão bibliográfica - D’agostin, Miguel Ângelo (Universidade do Vale do Rio dos Sinos, 2017)
In the searching for greater competitiveness, companies have invested in lean manufacturing tools implementation. However many questions have been asked regarding the application of these tools are generating wastes to the ergonomic working condition. Theaim of this article was to discuss such questions based on a theoretical review based on related in the last two years (2015/2016). The search platform used for the search was the Capes website. Findings shows no evidence about wastes regarding ergonomic aspects after the application of lean manufacturing tools. It is relevant to explain the goal of lean tools is to identify existing problems that usually companies do not perform deply regarding the relation between ergonomic and lean manufacturing. In addition, ergonomic analysis allows to evaluate working aspects not identified only by lean tools. In order to conclude, it can be inferred that tools focused on ergonomics and lean manufacturing should be implemented concomitantly, since they complement each other in the search for the best solution.
Keywords: Ergonomia; Manufatura enxuta; Ambiente de trabalho; Ergonomics; Lean manufacturing; Workplace